Smart Design for Evacuation Signage Layout for Exhibition Halls in Exhibition Buildings Based on Visibility - Zhanzhi Wan; Tiejun Zhou; Zhili Tang; Yin Pan; Lingfei Zhang (ISPRS International Journal of Geo-Information, 2021)
The reasonable placement of evacuation signage is an important means to improve the efficiency of evacuation in the exhibition halls of exhibition buildings. The booths in exhibition halls are arranged and changed frequently for different exhibitions, which means that the evacuation paths are not fixed. Most people are also unfamiliar with the exhibition hall environment. In case of fire, earthquake, or other emergencies, people need to quickly escape to the safety exit, adhering to the guidance of evacuation signage. Existing evacuation signs are located according to the standards and the experience of the designers, and the locations of the signs are fixed and do not change with the changes in the booth layout, which means that the signage can be easily obscured by the booths, affecting the signage identification. Based on the visibility of evacuation signage, a smart design method of evacuation signage layout is proposed in this paper that can be adapted to different forms of booth arrangements in exhibition halls. This method establishes a key goal of achieving the full coverage of the visibility range of evacuation passages with the minimum number of evacuation signs. In the context of the actual visibility range of evacuation signage being blocked by booths in a three-dimensional space, this method finds the optimal number and best locations of evacuation signs by using a genetic algorithm. Finally, a case is given to verify the effectiveness of the method. This smart design for evacuation signage layout can enhance the guidance ability of evacuation signage in exhibition halls and improve the efficiency of evacuation.